Tuesday
March 28, 2017

Post a New Question

Posted by on .

5-(t+3)=-1+2(t+3)
I don't know how to do it.
I need help going over the steps

  • math - ,

    You need to get t on one side.

    remove the ( )
    5-t-3=-1+2t+6
    UNDERSTAND that step, most beginning students err there.

    Then, add t to both sides
    5-3=-1+3t+6
    subtract 5 from both sides.-3=3t
    t=-1

    now go back to the original, put for t -1, and see if it checks.

  • math - ,

    The book says it's 3..

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question